Inovasi Media Pembelajaran E-Modul Interaktif Dasar Fisiologi Tumbuhan Berbasis Canva dan Educandy Studio Bagi Mahasiswa Agroekoteknologi - Wisnubroto, Muhammad Parikesit (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – Learning media innovation for basic plant physiology courses is needed in today's digital era, one of which is through e-modules based on Canva and Educandy Studio. Through this research, the effectiveness of e-module innovation based on the combination of Canva and Education Studio will be studied more deeply to find out how effective the development of a combination e-module is in improving student grades.Method – The study was conducted on 27 Agroecotechnology students, Universitas Andalas, who took the plant physiology course. E-modules and quizzes were created using Canva and Education Studio. The effectiveness of using e-modules is seen based on pre-test and post-test scores, which are analyzed by effect size analysis.Findings – The canva-based basic plant physiology e-module combined with game-based quizzes with Educandy studio can effectively increase student scores by 44.59%. The core material of the e-module is declared valid and feasible with a Cronbach's alpha value of 0.84. This innovation succeeded in increasing learning effectiveness by 89%. Research Implications – The innovation of e-modules based on canva and educandy studio as a basic learning of plant physiology can improve student understanding in each physiological process, especially the bright reaction of photosynthesis. This e-module provides a more attractive learning media display and provides an opportunity for students to evaluate independently. The limited features of Canva and Education Studio resulted in not all physiology material being poured in the form of e-modules. However, overall e-module innovation has a significant effect on the level of student understanding.